Evidence of multiple mechanisms providing carbamate and organophosphate resistance in field An. gambiae population from Atacora in Benin - Aikpon, Rock; SEZONLIN, MICHEL; Ossè, Razaki; Akogbéto, Martin (My University, 2014)
Background: Insecticide resistance in Anopheles gambiae s.l is a major concern to malaria vector control programmes. In West Africa, resistance is mainly due to target–site insensitivity arising from a single point mutation. Metabolic-based resistance mechanisms have also been implicated and are currently being investigated in west Africa. The aim of this study is to better understand the origins of carbamate and organophosphate resistance in An. gambiae population from Atacora, Benin in West Africa. Methods: Anopheles mosquitoes were reared from larvae collected in two districts (Kouandé and Tanguiéta) of the Atacora department. Mosquitoes were then exposed to WHO impregnated papers. Four impregnated papers were used: carbamates (0.1% bendiocarb, 0.1% propoxur) and organophosphates (0.25% pirimiphos methyl, 1% fenitrothion). PCR assays were run to determine the members of the An. gambiae complex, as well as phenotypes for insensitive acetylcholinesterase (AChE1). Biochemical assays were also carried out to detect any increase in the activity of enzyme typically involved in insecticide metabolism (oxidase, esterase and glutathion-S-transferase). Results: 769 female of An. gambiae mosquitoes from Kouandé and Tanguiéta were exposed to bendiocarb, propoxur, pirimiphos methyl and fenitrothion. Bioassays showed resistance with low mortality to bendiocarb (78.57% to 80.17%), propoxur (77.21% to 89.77%), and fenitrothion (89.74% to 92.02%). On the other hand, the same populations of An. gambiae from Kouandé and Tanguiéta showed high susceptibility to pirimiphos methyl with recorded mortality of 99.02% and 100% respectively. The low rate of ace-1R allele frequency (3.75% among survivors and 0.48% among dead) added to the high proportion of homozygous susceptible specimens which survived the WHO bioassays (8/28), suggest that the ace-1 mutation could not entirely explain Anopheles gambiae resistance to carbamate and organophosphate. Biochemical assays suggest that resistance in this population is mediated by metabolic resistance with elevated level of GST, MFO and NSE compared to a susceptible strain An. gambiae Kisumu. Conclusions: Anopheles gambiae populations resistance from Atacora is multifactorial and includes target-site mutation and metabolic mechanism. The co-implication of both resistance mechanisms in An. gambiae s.l may be a serious obstacle for the future success of malaria control operations based on LLINs and IRS.
Keywords: Resistance mechanisms; Carbamate; Organophosphate; Anopheles gambiae; Benin